Functional Characterization of the Maize Phytochrome-Interacting Factors PIF4 and PIF5 - Shi, Qingbiao; Zhang, Haisen; Song, Xiaoyi; Jiang, Yu’e; Liang, Ran; Li, Gang (Frontiers in Plant Science, 2018)
Phytochrome-Interacting Factors (PIFs) play important roles in photomorphogenesis, the shade avoidance response, and other aspects of plant growth and development. PIF family proteins have been well studied in Arabidopsis thaliana, but little is known about their physiological functions and molecular mechanisms in maize (Zea mays). In this study, we investigated the physiological functions of ZmPIF4 and ZmPIF5, two highly conserved members of the PIF gene family. RT-qPCR and western blot analyses revealed that ZmPIF4 and ZmPIF5 expression and ZmPIF4 and ZmPIF5 levels peak at night and remain low during the day. Overexpression of ZmPIF4 and ZmPIF5 in Arabidopsis partially rescued the reduced hypocotyl elongation and defective response to gravity in pif1 pif3 pif4 pif5 quadruple mutants (pifq). In addition, under high red: far-red light conditions, Arabidopsis lines overexpressing ZmPIF4 exhibited a constitutive shade avoidance response, including early flowering, slender leaves and inflorescences, plant lodging and precocious leaf senescence. Furthermore, ZmPIF4 physically interacted with the Arabidopsis DELLA protein REPRESSOR OF GA1-3 (RGA), indicating a potential interaction between ZmPIF4 and gibberellin signaling pathway on plant growth. Taken together, our results revealed that ZmPIF4 and ZmPIF5 are functionally conserved proteins that may play conserved roles in the response to phytochrome signaling in plants.